Virtual Authenticity: On Reinvention, Transformation and Functionality of Traditional Dancing during COVID-19 - Panova-Tekath, Gergana (Interdisciplinary Studies in Musicology, 2022)
The following article is dedicated to the changes in folk dancing caused by the Covid pandemic and presents the author’s theoretical ideas on dancing in the digital world. The examples concern the phenomenon of dancing the Bulgarian way by Bulgarians and non-Bulgarians in urban settings, which the author has been studying for years and now diagnoses the emergence of a new virtual model and defines virtual authenticity. On the one hand it relates to the fluid notion of authenticity and organises self-reflection, free expression and rediscovering of one’s own identity in cyberspace. Distance-dancing the Bulgarian way provides a psychosomatic environment with previously unknown online effects and paradoxical dichotomies. In this notion of subjective authenticity, the memory of the social intimacy of circle dancing helps with the social intimacy in the online communication and supports the belief in the whole world as an open community. On the other hand, in addition to focusing on themselves through constrained aloneliness, dancers also engage with themes of the political past, cultural essence and national determination. The verbal discussions in social networks, at virtual folk dance camps and in university classes reveal the solid notion of authenticity. Transparency leads to more knowledge about Bulgaria and its interpretations; endless accessibility improves the correctness of the sources. Nevertheless, the new roles and hierarchies in digital Bulgaria provoke vulnerability and emotion. Recognising the phenomenon as persuasive and flattering communication, the increased verbal exchange connects both the individual and community aspects of authenticity. Even if the dance enthusiasts from Bulgaria and from abroad are not yet fully united in the so-called imagined or digital Bulgaria, the phenomenon participates more than ever in the idea of a global village. Distance-dancing the Bulgarian way creates third spaces of protection and resistance and establishes a global community that has a future beyond the pandemic.